Producción de etanol a partir del bagazo residual de un proceso de fermentación alcohólica en planta piloto (2024)
"The project focuses on ethanol production from malt husks, a byproduct of the brewing industry, using an acid hydrolysis process followed by fermentation and distillation. Nine laboratory-scale hydrolyses were carried out, varying the reaction time (1, 3, and 5 hours) while keeping the temperature (80°C) and pH (1) constant. The hydrolyses conducted for 3 and 5 hours showed the best results in terms of the amount of carbohydrates released; however, for optimization purposes, the 3-hour hydrolysis was selected for process scaling. Subsequently, two groups of fermentations were performed, one with whisky yeast and the other with bread yeast, over a period of 15 days. Four distillations were carried out for each group: two simple distillations and two extractive distillations using glycerol. The results indicated that using whisky yeast yielded ethanol with a purity of 96% v/v and a yield of 1.94, while bread yeast achieved only a concentration of 54% v/v ethanol and a yield of 0.81. These results demonstrate the viability of using malt husks for efficient and sustainable ethanol production, particularly when employing whisky yeast. The project highlights the importance of ethanol in various industrial sectors, emphasizing its impact on the circular economy and the search for sustainable alternatives for development, contributing to the diversification of renewable energy sources and the utilization of byproducts from the brewing industry."